Andragogical Approach Based on Civic Education to Increase the Social Participation of Universitas Pamulang Students - Lina Marlina; Suranto Aw; Rhoma Dwi Aria Yuliantri; Ida Nuraida; Suanto (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2026)
This study is motivated by the limited research on the application of the andragogical approach in Civic Education at the higher education level, particularly regarding its contribution to strengthening students’ awareness and social participation. This research aims to describe the implementation of the andragogical approach and analyze its impact on students’ social participation at Universitas Pamulang. A descriptive qualitative method was employed, using observations, in-depth interviews, and open-ended questionnaires involving early-semester students and course lecturers. The findings reveal that the andragogical approach is implemented through the recognition of students’ prior experiences, critical discussions, problem-solving activities, case studies, community-based social projects, and reflective assessments conducted in the university library as an interactive dialogue space. These learning strategies were proven to enhance students’ abilities to express ideas, analyze social issues, and participate actively in both campus-based and community social activities. The study concludes that the andragogical approach effectively strengthens students’ critical awareness and social responsibility. The study recommends that the andragogical approach be used as a basis for developing learning strategies and designing curriculum policies that aim to improve students’ sustainable social participation across higher education institutions.